Marriage, parenthood and social network: subjective well-being and mental health in old age - Becker, Christoph; Kirchmaier, Isadora; Trautmann, Stefan T. (PLOS ONE, 2019)
Parenthood, marital status and social networks have been shown to relate to the well-being and mental health of older people. Using a large sample of respondents aged 50 and older from 16 European countries, we identify the associations of well-being and mental health with family status. Making use of detailed social network data of the respondents, we also identify how different social support networks correlate with the well-being and health indicators. We observe positive associations for all network types, over and beyond any direct associations of family status with well-being. Results suggest that non-residential children are important providers of social support for their parents at older age.